DAMPAK SISTEM PENGENDALIAN MANAJEMEN DAN GREEN ACCOUNTING TERHADAP KINERJA PERUSAHAAN PADA PERUMDA TIRTANADI SUMATERA UTARA - Parlindungan (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the impact of Management Control System and Green Accounting on company performance at Perumda Tirtanadi Sumatera Utara. Using a quantitative approach, 100 respondents were selected through probability sampling and data were analyzed using SmartPLS-based path analysis. Results show that the Management Control System positively and significantly affects company performance (path coefficient 0.385; T-statistic 11.005; p-value 0.000), while Green Accounting has a stronger positive effect (path coefficient 0.578; T-statistic 18.832; p-value 0.001). The R² value of 0.902 indicates that both variables explain 90.2% of the variation in company performance. Green Accounting is the most dominant variable in this study.